Hidradenitis Suppurativa : A Disease Primer - Kimball, Alexa B.; Jemec, Gregor B.E (Springer International Publishing : Imprint: Adis, 2017)
A concise but comprehensive pocket handbook that provides an accessible and up-to-date introductory overview of this debilitating skin disease. Written by highly recognizable leaders in the field, this book presents essential information on the pathophysiology, clinical presentation, diagnosis and management strategies and options for hidradenitis suppurativa, forming an ideal resource to increase awareness of this disease among healthcare professionals.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books